2007
DOI: 10.1073/pnas.0608765104
|View full text |Cite
|
Sign up to set email alerts
|

Distinct contribution of electrostatics, initial conformational ensemble, and macromolecular stability in RNA folding

Abstract: We distinguish the contribution of the electrostatic environment, initial conformational ensemble, and macromolecular stability on the folding mechanism of a large RNA using a combination of time-resolved ''Fast Fenton'' hydroxyl radical footprinting and exhaustive kinetic modeling. This integrated approach allows us to define the folding landscape of the L-21 Tetrahymena thermophila group I intron structurally and kinetically from its earliest steps with unprecedented accuracy. Distinct parallel pathways lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 52 publications
2
77
0
Order By: Relevance
“…Parallel advances have been made with a new and powerful footprinting approach called "SHAPE", which shows protection data for residues in secondary and tertiary structures [112][113][114]. New kinetic modeling approaches have greatly simplified and systematized the development of kinetic models from large sets of footprinting data; such an approach has been recently applied to characterize the folding pathways of wild type and mutant Tetrahymena group I intron [115,116].…”
Section: Rna: Present and Futurementioning
confidence: 99%
“…Parallel advances have been made with a new and powerful footprinting approach called "SHAPE", which shows protection data for residues in secondary and tertiary structures [112][113][114]. New kinetic modeling approaches have greatly simplified and systematized the development of kinetic models from large sets of footprinting data; such an approach has been recently applied to characterize the folding pathways of wild type and mutant Tetrahymena group I intron [115,116].…”
Section: Rna: Present and Futurementioning
confidence: 99%
“…Therefore, in order to address the relationship between topologically conserved tertiary interactions and folding pathways in RNA, we adopted a complementary quantitative approach that critically compares structural-kinetic folding models resolved from timeresolved hydroxyl radical ( d OH) footprinting experiments on structurally homologous RNA molecules. Structural-kinetic folding models, by providing insight into the dominant folding pathways, structural features of the folding intermediates, and their solution lifetimes Shcherbakova and Brenowitz 2008), have helped elucidate the contributions of both physical and intrinsic factors that influence RNA folding mechanisms (Laederach et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…The stabilization of the nonspecific collapsed state slows down the (productive) folding to the final native state which requires the formation and stabilization of specific native contacts [49,67]. In addition, a recent experiment showed that, depending on the ionic condition of the solution, the kinetic partitioning of the folding flux can be dependent on the initial conformational ensemble [68].…”
Section: Tetrahymenamentioning
confidence: 99%
“…By lowering the electrostatic barrier for the kinetics, ions can promote the kinetic process of RNA folding and control the folding rate and pathways. There have been tremendous experimental efforts on the role of metal ions in RNA (and DNA) folding kinetics (see Table 4) at both secondary and tertiary structural levels [20,[61][62][63][64][65][66][67][68].…”
Section: Diffuse Ion Is Critical To Rna Folding Kineticsmentioning
confidence: 99%